Planting design connecting people and place - Mooney, Patrick, 1949- (Routledge, 2020)
Landscape designers have long understood the use of plants to provide beauty, aesthetic pleasure and visual stimulation while supporting a broad range of functional goals. However, the potential for plants in the landscape to elicit human involvement and provide mental stimulation and restoration is much less well understood. This book meshes the art of planting design with an understanding of how humans respond to natural environments. Beginning with an understanding of human needs, preferences, and responses to landscape, the author interprets the ways in which an understanding of the human- environment interaction can inform planting design. Many of the principles and techniques that may be used in planting design are beautifully illustrated in full colour with examples by leading landscape architects and designers from the United Kingdom, Europe, North America and Asia including Andrea Cochran, Richard Hartlage, Melody Redekop, Shunmyo Masuno, Allyson Mendenhall, Piet Oudolf, Christine Ten Eyck and Kongjian Yu. The book stimulates thought, provides new direction and assists the reader to find their own unique design voice. Because there are many valid processes and intentions for landscape design, the book is not intended to be overly prescriptive. Rather than presenting a strict design method and accompanying set of rules, Planting Design provides information, insight and inspiration as a basis for developing the individual designer's own expression in this most challenging of art forms".